2023
DOI: 10.1002/ejoc.202300969
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzoylperoxide‐Mediated Oxidative α‐Thio/Seleno‐Cyanation of β‐Ketoesters and Oxindoles

Christopher Mairhofer,
Katharina Röser,
Meysam Aryafard
et al.

Abstract: We herein report a protocol for the α‐thio‐ and α‐seleno‐cyanation of different cyclic β‐ketoesters and oxindoles by using NaSCN or KSeCN as easily accessible inorganic nucleophilic S(e)CN sources under oxidative conditions. Key to success for both transformations is the use of dibenzoylperoxide as an oxidant allowing for the coupling of two inherently nucleophilic species under operationally simple conditions in high yields and with broad functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…We started our investigations by optimizing the α-azidation of the tert -butyl-containing β-ketoester 1a ( Table 1 gives an overview of the most significant results obtained hereby). First experiments testing different oxidants in combination with Bu 4 NI (30 mol %) in 1,2-dichloroethane (DCE), a solvent that we found to be well-suited for oxidative α-heterofunctionalizations before [ 39 ], showed that DBPO clearly outperforms all the other oxidants tested under these conditions ( Table 1 , entries 1–5). While H 2 O 2 gave 2a in low yield only ( Table 1 , entry 1), the use of mCPBA ( Table 1 , entry 3) and t -BuOOH ( Table 1 , entry 4) mainly resulted in the formation of the α-OH-ketoester 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We started our investigations by optimizing the α-azidation of the tert -butyl-containing β-ketoester 1a ( Table 1 gives an overview of the most significant results obtained hereby). First experiments testing different oxidants in combination with Bu 4 NI (30 mol %) in 1,2-dichloroethane (DCE), a solvent that we found to be well-suited for oxidative α-heterofunctionalizations before [ 39 ], showed that DBPO clearly outperforms all the other oxidants tested under these conditions ( Table 1 , entries 1–5). While H 2 O 2 gave 2a in low yield only ( Table 1 , entry 1), the use of mCPBA ( Table 1 , entry 3) and t -BuOOH ( Table 1 , entry 4) mainly resulted in the formation of the α-OH-ketoester 4 .…”
Section: Resultsmentioning
confidence: 99%
“…These oxidative approaches, which usually proceed via the in situ formation of catalytically-competent ammonium hypoiodite species, can normally be carried out under operationally simple conditions, thus allowing for the use of easily accessible starting materials. Our group has a longstanding research interest in α-heterofunctionalization reactions under oxidative conditions [ 37 39 ] and we [ 30 ], as well as others [ 28 29 31 ], have recently also explored the use of simple quaternary ammonium iodides for oxidative α-azidations of carbonyl compounds ( Scheme 1A ). Hereby different strategies using different quaternary ammonium iodide derivatives and different azide sources were investigated and especially Uyanik’s and Ishihara’s recent approach using NaN 3 in combination with the carefully designed achiral catalyst C1 represents a remarkable advancement in this field ( Scheme 1B [ 31 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations